The Realities of Learning through Failure in Entrepreneurship: Results of Qualitative Research - Mtibaa, Nizar; Boudabbous, Sami (International Review of Management and Marketing, 2023)
In this research work, we sought to conceptualize the existing relationship between entrepreneurial learning and failure. By exploring the theoretical models of entrepreneurial learning, particularly those of Cope (2005) and Politis (2005), we identified three major research proposals that we confronted with reality by conducting an exploratory qualitative study with 10 Tunisian entrepreneurs who had experienced failure during their entrepreneurial activity. Through this study, we retained that failure constitutes an opportunity for entrepreneurial learning that manifests itself as a continuous process where the emotions of the entrepreneur play an important role. This learning depends on the nature of the failure, the emotions and the emotional regulators.